Type 2 diabetes mellitus and atherogenic dyslipidemia: Which statin is most effective in the primary prevention of cardiovascular events? - Figg, Gemma (2012)
Background: Type 2 diabetics are at high risk of atherosclerosis and cardiovascular (CV) events due to their associated dyslipidemic profile. Adverse levels of the lipid triad: low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TGs), have been shown to be major contributing factors. Statins (HMG-CoA reductase inhibitors) are recommended as first-line lipid therapy as evidence has shown their effectiveness in primary and secondary prevention of CV events. However, there is limited evidence specifically focused on primary prevention in type 2 diabetes mellitus (T2DM) and dyslipidemia. Objective: To assess the efficacy of statins in type 2 diabetics with dyslipidemia for the primary prevention of CV events. Methods: A systematic review was carried out to determine the effectiveness of statins in T2DM and dyslipidemia. A comprehensive literature search identified randomised control trials (RCTs) specific to participants with T2DM and dyslipidemia without prior CV events, which investigated the effects of statins on the lipid triad. Bias and quality of the studies were assessed and data extracted was critically analysed. Meta-analyses were carried out to determine the significance of statin effects. Results: 10 RCTs were included investigating the effects of six statins. Statins were shown to improve the lipid triad by lowering LDL-C and TGs and increasing HDL-C, in agreement with previous research. Atorvastatin and rosuvastatin were shown to be most potent in reducing LDL-C and TGs and simvastatin showed the greatest increases in HDL-C. Meta-analyses demonstrated significance favouring statins for LDL-C and TG reductions but less evidence of significant effect of HDL-C VII improvement with all statins. Statins were well tolerated and adverse effects were minimal. Conclusion: Primary prevention in this high risk population is very important. Statins are effective at reducing CV event risk, and nurses should have knowledge of most appropriate statin treatments for patients based on individual lipid levels